2016
DOI: 10.1158/1538-7445.am2016-3975
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3975: Matrix-depleting anti-hypertensives decompress tumor blood vessels and improve perfusion in patients with glioblastomas receiving anti-angiogenic therapy

Abstract: Introduction: Impaired tumor perfusion is associated with poor drug delivery, hypoxia and metastatic behavior that effectively make cancers difficult to treat [1]. A main driver of impaired perfusion in permeable and impermeable tumor vessels is solid stress caused by proliferating tumor cells and the extracellular matrix that squeeze vessels shut [2]. Here, we demonstrate improved vascular function in glioblastoma patients who receive hypertension treatments with an anti-cancer cell, matrix-depleting effect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For example, angiotensin system inhibition (ASI) with losartan inhibits downstream profibrotic pathways—TGF-β1, connective tissue growth factor, endothelin-1—in CAFs, and thereby reduces solid stress, decompresses vessels, and increases oxygen and drug delivery without increasing malignancy (Chauhan et al 2013). There is evidence of ASI-induced vessel decompression in glioblastoma patients (Emblem et al 2016). Besides decompressing vessels, as TGF-β1 promotes protumor immune suppression (Wrzesinski et al 2007; Pickup et al 2013; Papageorgis and Stylianopoulos 2015), losartan reduces metastasis by blocking monocyte recruitment (Regan et al 2016).…”
Section: Strategies To Alleviate Hypoxia and Overcome Heterogeneitymentioning
confidence: 99%
“…For example, angiotensin system inhibition (ASI) with losartan inhibits downstream profibrotic pathways—TGF-β1, connective tissue growth factor, endothelin-1—in CAFs, and thereby reduces solid stress, decompresses vessels, and increases oxygen and drug delivery without increasing malignancy (Chauhan et al 2013). There is evidence of ASI-induced vessel decompression in glioblastoma patients (Emblem et al 2016). Besides decompressing vessels, as TGF-β1 promotes protumor immune suppression (Wrzesinski et al 2007; Pickup et al 2013; Papageorgis and Stylianopoulos 2015), losartan reduces metastasis by blocking monocyte recruitment (Regan et al 2016).…”
Section: Strategies To Alleviate Hypoxia and Overcome Heterogeneitymentioning
confidence: 99%
“…A retrospective analysis in glioblastoma found that angiotensin system inhibitors (ASIs), which are agents shown to decompress vessels in preclinical models, also did so in patients. Specifically, small vessels were reperfused (45). This result is supported by finding in a retrospective study that patients who took ASIs to manage hypertension either pretreatment or after bevacizumab had improved overall survival (46).…”
Section: Oxygenation Is the Critical Biomarker For Patient Outcomes Amentioning
confidence: 99%
“…Thus, we hypothesize that maximizing decompressed MVD before AAT will improve outcomes. In glioblastoma patients, ASIs increased the amount of perfused vessels by reperfusing small vessels (45). Indeed, retrospective studies of glioblastoma patients indicate that ASIs alone and in combination with bevacizumab and/or chemotherapy increase survival of patients (46).…”
Section: Normalization—not Destruction—of the Tumor Microenvironment mentioning
confidence: 99%
“…In an orthotopic model of PDAC, inhibition of aberrant TGF-β signaling by losartan restored vessel diameter and permeability ( 60 ). In a retrospective study of glioblastoma patients receiving anticancer therapy, a concomitant treatment with matrix-depleting antihypertensive drugs improved vascular function as assessed by magnetic resonance imaging ( 75 ). The impaired perfusion and hypoxic condition of tumors can be further aggravated by AngII-induced vasoconstriction and increased vascular resistance ( Fig.…”
Section: Introductionmentioning
confidence: 99%